Effects of Different Gastrointestinal Surgical Approaches on Pancreatic β-cell Function in Type 2 Diabetic Patients with BMIs<30 - Lubai, X.; Kejia, W.; Jingli, C.; Zhenzhai, C.; Baoqing, L; Jisheng, W.; Bing, Z.; Hai, H (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objective: Gastrointestinal surgery has been performed for many years to achieve durable and effective treatments of type 2 diabetes mellitus (T2DM). This study determined the effects of different surgical operations on pancreatic β-cell function in patients with T2DM with BMIs<30 kg/m2.Design and patients: A total of 46 patients with diabetes and BMIs<30 kg/m2 underwent gastrointestinal surgery; 23 patients underwent Roux-en-Y gastric bypass (RYGB), and 23 patients underwent Billroth Ι gastrectomy (BΙG). Oral glucose tolerance tests were used to evaluate pancreatic β cell function. Serum insulin was measured by enzyme-linked immunosorbent assay (ELISA), and blood glucose was detected with the glucose oxidase method. HOMA-IR and HOMA-β were evaluated with the HOMA equation.Results: The T2DM remission rates were 21.7% (5/23) in the BΙG group and 82.6% (19/23) in the RYGB group. There was a significant difference in the improvements in postoperative glycosylated hemoglobin A1c (GHbA1c) and glycated hemoglobin A1 (GHbA1) between the BΙG and RYGB groups (P=0.001, P=0.002). OGTT revealed that both fasting blood glucose (FBG) and blood glucose at the designated time points after glucose loading were significantly lower in the RYGB group than in the BΙG group. Insulin levels (at 30 and 60 min), insulin release indices (at 30 and 60 min), HOMA-β and ΔI30/ΔG30 were significantly higher in the RYGB group than in the BΙG group (P<0.05).Conclusions: Patients with BMIs<30 kg/m2 who underwent RYGB surgery exhibited significantly greater improvements or resolutions of T2DM and significantly better recoveries of β-cells function than did those in the BΙG group.
Keywords: gastrectomy; bariatric surgery; type 2 diabetes mellitus; β-cell function